Efficacy of lactulose in the prophylaxis of hepatic encephalopathy in cirrhotic patients presenting gastrointestinal bleeding - Aires,Felipe Toyama (2016)
SUMMARY Introduction: Hepatic encephalopathy (HE) is a bad prognostic factor in patients with liver cirrhosis and its incidence is associated with several triggering factors being the most prevalent gastrointestinal bleeding. Lactulose, despite its questionable efficacy in the literature, is considered a first line treatment in patients with HE. Objective: To evaluate the effectiveness of lactulose in preventing HE in cirrhotic patients with gastrointestinal bleeding. Method: A systematic review of the literature using the Medline scientific database. Only randomized controlled clinical trials evaluating the efficacy of lactulose for HE prophylaxis in cirrhotic patients with gastrointestinal bleeding were included. Results: The incidence of HE in the intervention group was 7%, while the control group was 26% (p=0.01). There was no significant difference in the incidence of mortality in the group treated with lactulose compared to the group that was not treated (p=0.48). Conclusion: Administering lactulose to cirrhotic patients with upper gastrointestinal bleeding reduces the incidence of hepatic encephalopathy.